تيسير تعلم اللغة العربية والدّراسات الإسلامية عند اللغويّين الحديثين - Andi Holilulloh; Ashom Mushtofa Ahmad (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2020)
Arabic syntax (nahwu) is an Arabic science that we learn to understand the science of religion (Islamic studies) and it is also related to the Holy Qur’an. The manifestations of renewal seemed to Mahdi Al-Makhzoumi and Tammam Hassan in calling to revive the integrated arabic syntax which levels are linked, and the learners specialize for one purpose, which is the Arabic lesson. The new Arabic syntax (nahwu) of Mahdi Al-Makhzoumi and Tammam Hassan in their opinions on Arabic syntax (nahwu) related to Islamic studies because arabic syntax has come out of the Holy Qur’an. Renewal arabic syntax (nahwu) has a benefit to make simple and to facilitate the teaching of the Arabic language and Islamic studies because it is a necessity of time as we knew that we are now in modern era. The important argument of ours to know about simplifying Arabic syntax that is renewal Arabic syntax, there is a solution to the difficulty of understanding Arabic syntax (nahwu), and perhaps this is the revival of Arabic syntax (nahwu). Mahdi Al-Makhzoumi was influenced by Khalil ideas (Khalil bin Ahmad Al-Farahidi), and the Arabic syntax thoughts of Kufa (the school of Kufa). Tammam Hassan was influenced by thoughts of Abdul Qahir al-Jurjani and western linguistic which outputs theory of Tadhafur al-Qara’in. The approaches of Makhzoumi and Hassan in simplifying Arabic syntax (nahwu) divided into two parts: theoretical and practical, but the practical approach in simplifying grammar, for example, cancellation of qiyas and rejection of ‘ilal (ta’lil), then re-tabulation of Arabic syntax topics etc.